2022
DOI: 10.3389/fmars.2022.930911
|View full text |Cite
|
Sign up to set email alerts
|

Trend detection by innovative polygon trend analysis for winds and waves

Abstract: It is known that densely populated coastal areas may be adversely affected as a result of the climate change effects. In this respect, for coastal protection, utilization, and management it is critical to understand the changes in wind speed (WS) and significant wave height (SWH) in coastal areas. Innovative approaches, which are one of the trend analysis methods used as an effective way to examine these changes, have started to be used very frequently in many fields in recent years, although not in coastal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…In the improved visualization of ITA (IV-ITA) method proposed by Güçlü (2020) [51], the data can be statistically categorized as low values and high values by applying the Pettitt change point test to the differences of the time series that are divided into two halves and ranked in ascending order. Detailed information about the ITA, IPTA, IPTA with star graph, and IV-ITA methods can be found in Acar et al (2022Acar et al ( , 2023 [26,35] and Akçay et al (2022) [25].…”
Section: Innovative Trend Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the improved visualization of ITA (IV-ITA) method proposed by Güçlü (2020) [51], the data can be statistically categorized as low values and high values by applying the Pettitt change point test to the differences of the time series that are divided into two halves and ranked in ascending order. Detailed information about the ITA, IPTA, IPTA with star graph, and IV-ITA methods can be found in Acar et al (2022Acar et al ( , 2023 [26,35] and Akçay et al (2022) [25].…”
Section: Innovative Trend Analysis Methodsmentioning
confidence: 99%
“…In previous studies, researchers generally used the classical Mann-Kendall test, Theil-Sen method, and linear regression analysis. Apart from classical methods, the innovative trend analysis (ITA) method, suggested by Şen (2012) [34], the innovative polygon trend analysis (IPTA), the improved visualization of ITA (IV-ITA), and star graph methods based on ITA have been the basis for several recent studies (Acar et al, 2022(Acar et al, , 2023; Akçay et al, 2022) [25] and have provided greater clarity in the perception of long-term climatic trends. The innovative methods are open to the visual interpretation of the results, do not contain assumptions such as normal distribution and serial dependence, etc., and are easy to apply.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this method is capable of uncovering monthly and seasonal variations that may not be detected by the traditional annual hydrometeorological analysis (Sen et al, 2019). Several studies currently apply the IPTA technique and suggest its capacity for exploring the hidden trends that occur during the holistic annual trend detection approach (Akcay et al, 2022;Esit, 2023;Sen et al, 2019). Akcay et al (2022) applied both IPTA and Man Kendall (MK) for trend analysis of winds and waves and indicated that the IPTA method is more sensitive and detects more trends than the MK method.…”
Section: Innovative Polygon Trend Analysis (Ipta)mentioning
confidence: 99%
“…In the Shandong plain regions, the highest significant increasing trend is identified at the Dingtao station in January (39.3%), whereas the maximum significant decreasing trend is recorded at the Heze station in December (180.4%). Several studies currently apply the IPTA technique and suggest its capacity for exploring the hidden trends that occur during the holistic annual trend detection approach (Akcay et al, 2022;Esit, 2023;Sen et al, 2019). Akcay et al (2022) applied both IPTA and Man Kendall (MK) for trend analysis of winds and waves and indicated that the IPTA method is more sensitive and detects more trends than the MK method, which aligns with these study results.…”
Section: Ipta Testmentioning
confidence: 99%
See 1 more Smart Citation